Performance and color of broilers fed diets containing Rhodocyclus gelatinosus biomass - Ponsano,EHG (2004)
The objective of this study was to evaluate the effect of different supplementation levels of Rhodocyclus gelatinosus biomass on the performance and pigmentation of broilers. Cobb broilers were raised in pens and were fed a sorghum-based diet until 35 days of age. At the 36th day of age, ninety-six birds were randomly distributed to four treatments consisting of experimental diets with different supplementation levels of Rhodocyclus gelatinosus biomass (0, 75, 150 and 300 ppm) added to the finisher basal diet, which were given for seven days. A completely randomized experimental design was used, with four treatments, four replicates and six broilers per parcel. Birds and diets were weighed at the 36th and at the 42nd day of age for performance analysis. There was no significant effect on broiler feed intake. Significant differences in weight gain and feed conversion were seen between the control group and the groups supplemented with 75 and 150 ppm. The treatment with the highest supplementation level and the control group had best weight gain and feed conversion. Color analysis showed that R. gelatinosus biomass supplementation resulted in more yellow breast skin and increased darkening and color purity in breast and thigh meat of broilers, but had no effect on lightness or color purity of breast and thigh skins.